Improvement of the Public Participation Waste Management System in Banda Aceh City - Ana Zahara; Dyah Kuntorini Dwi Angreni (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2023)
This study investigates how changing environmental governance in Banda Aceh City can benefit from public participation. The secret to improving environmental governance is figuring out how to involve the public, businesses, and government in the process. The interaction and influencing factors among enterprise pollution control, government oversight, and public engagement are examined using evolutionary game theory, and an empirical study is conducted using data from Banda Aceh City from 2017 to 2021. The findings of the study demonstrate that government oversight has a favorable impact on environmental governance and can motivate businesses to aggressively reduce pollution. The income and cost of businesses limit the impact of government regulation, hence it is necessary to increase the fines for passive pollution control. Enhancing the government's reputational damage can also effectively encourage environmental oversight activity on the part of the government. Three industrial wastes are substantially better governed when the public participates, and the cost and psychological advantages of involvement have a strong correlation with public enthusiasm. To some extent, public participation can take the place of governmental control. Environmental governance benefits from interactions between the public and the government. The study's findings will enhance environmental governance performance and public satisfaction while assisting in the development of an efficient system.